ESRP1 and ESRP2 are epithelial cell-type-specific regulators of FGFR2 splicing. - Warzecha, C.C.; Sato, T.K.; Nabet, B.; Hogenesch, J.B.; Carstens, R.P. (Molecular Cell, 2009)
Cell-type-specific expression of epithelial and mesenchymal isoforms of Fibroblast Growth Factor Receptor 2 (FGFR2) is achieved through tight regulation of mutually exclusive exons IIIb and IIIc, respectively. Using an application of cell-based cDNA expression screening, we identified two paralogous epithelial cell-type-specific RNA-binding proteins that are essential regulators of FGFR2 splicing. Ectopic expression of either protein in cells that express FGFR2-IIIc caused a switch in endogenous FGFR2 splicing to the epithelial isoform. Conversely, knockdown of both factors in cells that express FGFR2-IIIb by RNA interference caused a switch from the epithelial to mesenchymal isoform. These factors also regulate splicing of CD44, p120-Catenin (CTNND1), and hMena (ENAH), three transcripts that undergo changes in splicing during the epithelial-to-mesenchymal transition (EMT). These studies suggest that Epithelial Splicing Regulatory Proteins 1 and 2 (ESRP1 and ESRP2) are coordinators of an epithelial cell-type-specific splicing program.